2017
DOI: 10.1371/journal.pntd.0005408
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of Orientia tsutsugamushi genotypes by intragenic recombination and their potential expansion in endemic areas

Abstract: BackgroundScrub typhus is a mite-borne febrile disease caused by O. tsutsugamushi infection. Recently, emergence of scrub typhus has attracted considerable attention in several endemic countries in Asia and the western Pacific. In addition, the antigenic diversity of the intracellular pathogen has been a serious obstacle for developing effective diagnostics and vaccine.Methodology/Principal findingsTo understand the evolutionary pathway of genotypic diversification of O. tsutsugamushi and the environmental fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(92 citation statements)
references
References 84 publications
1
91
0
Order By: Relevance
“…The diverse microbiomes of chiggers add a further layer to the network of potential interactions that Orientia is exposed to, and future studies should determine whether some of these commensal bacteria affect chigger vector competence. Moreover, the positive correlation we identified here between chigger species richness and scrub typhus incidence deserves further investigation in other endemic countries, especially in relation to the epidemiology of Orientia strain diversity [48].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diverse microbiomes of chiggers add a further layer to the network of potential interactions that Orientia is exposed to, and future studies should determine whether some of these commensal bacteria affect chigger vector competence. Moreover, the positive correlation we identified here between chigger species richness and scrub typhus incidence deserves further investigation in other endemic countries, especially in relation to the epidemiology of Orientia strain diversity [48].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, more than 20 species of Leptotrombidium have been reported from Thailand, many only from the northern provinces where scrub typhus incidence is highest [13]. Although the majority of these species are not known to be scrub typhus vectors, recent data on vector competence are lacking, and it is plausible that transmission of O. tsutsugamushi by two or more vectors in the same region may contribute to diversification of the pathogen and an increase in human cases, as has been recently hypothesised for Taiwan [45, 48]. We also observed that human scrub typhus incidence was negatively associated with host-parasite network connectance, suggesting that increasing complexity of chigger-host interactions might reduce human exposure by zooprophylaxis, or lead to a greater likelihood that non-vector species dominate networks.…”
Section: Discussionmentioning
confidence: 99%
“…Orientia is an important bacterial pathogen with higher risk of infection for human population. Around one third of the population in the world is at risk of attaining the infection of Ott , emphasizing the importance of pathogen in global health . It was previously documented that metabolic pathway proteins are best suitable drug or vaccine targets .…”
Section: Discussionmentioning
confidence: 99%
“…Around one third of the population in the world is at risk of attaining the infection of Ott, emphasizing the importance of pathogen in global health. 52 It was previously documented that metabolic pathway proteins are best suitable drug or vaccine targets. 53 Few studies were performed in order to search protein targets in Ott 54 ; however, unique pathway proteins of Ott have not been analyzed till date for therapeutic targets.…”
Section: D-structure Modeling and Energy Minimizationmentioning
confidence: 99%
“…15 Recent studies also indicated that more divergent genotypes of O. tsutsugamushi prevail in Taiwan compared with other endemic countries in the Asian-Pacific region. 16,17 Therefore, it is necessary to consider the impact of broad genetic diversity of TSA gene of O. tsutsugamushi strains on diagnosis of scrub typhus in Taiwan.…”
Section: Introductionmentioning
confidence: 99%